Spandrel panels in masonry buildings: Effectiveness of the diagonal strut model within the equivalent frame model. (October 2020) - Sandoli, Antonio; Musella, Christian; Piero Lignola, Gian; Calderoni, Bruno; Prota, Andrea
Abstract: Modeling of masonry buildings subjected to seismic actions still represents an open problem in structural engineering. The equivalent frame model is the most used approach to analyze the seismic behavior of both existing and new masonry constructions but, despite this, several aspects are being researched to improve its effectiveness. Among these, modeling of spandrel panels plays a key role to correctly analyze the in-plane seismic response of unreinforced masonry walls. Actually, horizontal mono-dimensional beam-like elements provided of both strength and displacement capacity are used to schematize the spandrel panels, also according with the most of current national and international codes. In this paper an alternative strut and tie scheme to model the spandrel panels, suitable to be used within the equivalent frame approach, is presented: the compressed masonry material is schematized with an equivalent diagonal no-tension truss, whose length and effective compressed area are obtained with limit equilibrium conditions, while tensile-resistant element is represented by no-compression truss. Such model allows a more realistic representation of the mechanical behavior of spandrels because both amount of axial force within the spandrel and the reduced elastic flexural and shear stiffness due to progressive cracking of material are taken into account. Moreover, the local failures of both compressed masonry and/or tensile-resistant elements are better identified and, consequently, also the failure mechanisms of the whole equivalent frame are better detailed. The proposed schematization has been used to simulate the seismic behavior of some reference case studies of existing masonry walls, strengthened with different steel ties arrangement. These walls have been modelled with a hybrid equivalent frame model which consists of mono-dimensional beam-like element for piers, fully rigid offsets for the nodal panels and a strut and tie scheme for spandrels.